Neural Constraints Affect the Ability to Generate Hip Abduction Torques When Combined With Hip Extension or Ankle Plantarflexion in Chronic Hemiparetic Stroke - Sánchez, Natalia; Acosta, Ana M.; López-Rosado, Roberto; Dewald, Julius P. A. (Frontiers in Neurology, 2018)
Stroke lesions interrupt descending corticofugal fibers that provide the volitional control of the upper and lower extremities. Despite the evident manifestation of movement impairments post-stroke during standing and gait, neural constraints in the ability to generate joint torque combinations in the lower extremities are not yet well determined. Twelve chronic hemiparetic participants and eight age-matched control individuals participated in the present study. In an isometric setup, participants were instructed to combine submaximal hip extension or ankle plantarflexion torques with maximal hip abduction torques. Statistical analyses were run using linear mixed effects models. Results for the protocol combining hip extension and abduction indicate that participants post-stroke have severe limitations in the amount of hip abduction torque they can generate, dependent upon hip extension torque magnitude. These effects are manifested in the paretic extremity by the appearance of hip adduction torques instead of hip abduction at higher levels of hip extension. In the non-paretic extremity, significant reductions of hip abduction were also observed. In contrast, healthy control individuals were capable of combining varied levels of hip extension with maximal hip abduction. When combining ankle plantarflexion and hip abduction, only the paretic extremity showed reductions in the ability to generate hip abduction torques at increased levels of ankle plantarflexion. Our results provide insight into the neural mechanisms controlling the lower extremity post-stroke, supporting previously hypothesized increased reliance on postural brainstem motor pathways. These pathways have a greater dominance in the control of proximal joints (hip) compared to distal joints (ankle) and lead to synergistic activation of musculature due to their diffuse, bilateral connections at multiple spinal cord levels. We measured, for the first time, bilateral constraints in hip extension/abduction coupling in hemiparetic stroke, again in agreement with the expected increased reliance on bilateral brainstem motor pathways. Understanding of these neural constraints in the post-stroke lower extremities is key in the development of more effective rehabilitation interventions that target abnormal joint torque coupling patterns.